Ternate Tourism and Environmental Resource Center - Dela Cruz, Summer J. Len Reese A. (College of Architecture, University of the Philippines Diliman, 2018)
Mt. Palay Palay Mataas Na Gulod Protected Landscape is a little known ecotourism haven in the deep forested areas of Ternate, Cavite. Underdeveloped and neglects, the project aims to maximize the landscapes full potential in order to reconnect the people of Ternate with their community, rehabilitate the environmentally critical areas or the mountain, and revitalize not only the landscape, but also the town as nature lover's paradise. These goals were addressed through education and focusing the purpose of development as a learning facility. Using David Kolb's model for the Experiential Learning Cycle, the building's spaces have been divided into four learning zones- (1) abstract conceptualization, (2) active experimentation, (3) concrete experience, and (4) reflective observation. The users of the buildings go through the cycle as they move through the spaces and it culminates with their reflection on their learning as they leave the development. BINHI is the result of this project - a tourism and environmental resource center for Ternate on the Mt. Palay Mataas Na Gulod Protected landscape. The development serves as a gateway to the entore protected area, offering interesting views of the landscape, and showcasing the many features that make the area truly worth seeing.